Increasing Organizational Citizenship Behavior Through Strengthening Transformational Leadership in High School Teachers - Rohimah; Bibin Rubini; Widodo Sunaryo (CV ODIS, 2022)
Building human resources is a major responsibility of a country and it is a process that must be carried out sustainably, starting from the preschool, primary, secondary, and tertiary levels. The level of learning cannot guarantee the competitive advantage of human resources in Indonesia to compete against other countries in this era of global competition. One of the government's ways to balance the competition is to create a nine-year compulsory education program while improving systems, facilities, and infrastructure in educational institutions. Human resources or foreign terms are often referred to as